Good Governance as a Mediating Effect of Environmental Usage and Belief System in Enhancing the Acceptance of Lebanese Towards Malaysian Peacekeepers - Nordin, N. N. H.; Husin, W. N. W.; Salleh, M. Z. (International Journal of Social Science Research, 2024)
The United Nations (UN) has made a significant contribution to maintaining the security of people around the world. Through the role of peacekeeping operations, many countries that have just ended the conflict, such as Somalia, Nigeria, and Iraq, have been visited in order to help the locals rebuild their infrastructure. Nevertheless, in achieving these goals, some of the peacekeeping missions have faced difficulties due to a lack of exposure in understanding the cultural patterns and problems faced by the host people, and as a result, they are less accepted by the locals. This challenge is also caused by the weakness of the implementation of good governance for a country in managing peacekeeping missions, such as providing information on the culture, religion, and customs of the host people and the political structure and ethnic composition of a population. In this case, it was found that most Malaysian peacekeepers are less faced with difficulties, and they are usually welcomed by locals in every peacekeeping operation, including in Lebanon. Hence, the main objective of this study is to analyses the role of good governance as the mediating effect of the acceptance of the host people. Therefore, this study used two civil-military interaction (CMI) elements: environmental usage and belief systems mediated by good governance, to investigate the Lebanese acceptance of Malaysian peacekeepers. Therefore, a set of questionnaires was conducted in Maarakeh and Tebnine, involving 532 Lebanese. The findings showed that good governance positively influences environmental usage and belief systems, thus the Lebanese’s acceptance of Malaysian peacekeepers.